Effect of the Danish return-to-work program on long-term sickness absence: results from a randomized controlled trial in three municipalities - Otto Melchior Poulsen; Birgit Aust; Jakob Bue Bjorner; Reiner Rugulies; Jørgen V Hansen; Torill Tverborgvik; Glen Winzor; Ole Steen Mortensen; Trine Helverskov; Palle Ørbæk; Maj Britt D Nielsen (Nordic Association of Occupational Safety and Health (NOROSH), 2014)
OBJECTIVES: The aim of this study was to evaluate the effect of the Danish return-to-work (RTW) program on long-term sickness absence in a randomized controlled trial in three municipalities. METHODS: The intervention group comprised 1948 participants while the control group comprised 1157 participant receiving ordinary sickness benefit management (OSM). Study participants were working-age adults receiving long-term (≥8 weeks or more) benefits, included regardless of reason for sickness absence or employment status. Each beneficiary was followed-up for a maximum period of 52 weeks. Cox proportional hazards model was used to estimate hazard ratios (HR) for return to work (RTW) with 95% confidence intervals (95% CI). RESULTS: The intervention effect differed significantly between the municipalities (P=0.00005). In one municipality (M2) the intervention resulted in a statistically significant increased rate of recovery from long-term sickness absence (HR 1.51, 95% CI 1.31-1.74). In the other two municipalities, the intervention did not show a statistically significant effect (HR_M1 1.12, 95% CI 0.97-1.29, and HR_M3 0.80, 95% CI 0.63-1.03, respectively). Adjustment for a series of possible confounders only marginally altered the estimated HR. CONCLUSION: The effect of the intervention differed substantially between the three municipalities, indicating that that contextual factors are of major importance for success or failure of this complex intervention.